RANCANGAN SMART DOOR WITH AUTOMATIC LOCK SYSTEM: PINTU CERDAS BERSENSOR UNTUK MENGUKUR SUHU TUBUH DAN PEMBATASAN JUMLAH PENGUNJUNG - Endah Widiya Ningrum; Arif Budiarto; Yoga Purnama Putra; Ainur Komariah (Journal of Research and Technology Studies, 2022)
The COVID-19 pandemic continues, however, community activities are slowly starting to work as they should. Various places to eat and restaurants have reopened. Various efforts have been made by the government to reduce the spread of COVID-19. However, the level of community compliance in implementing health protocols in daily life has actually decreased, especially in terms of social distancing. To overcome this, the idea of ​​​​a Smart Door With Automatic Lock System was conceived – a Sensory Smart Door to Measure Body Temperature and Limit the Number of Visitors. In an effort to minimize the occurrence of crowds and reduce the number of excessive visitors by limiting 50% of the room capacity at the restaurant so as to minimize the number of Covid-19 transmissions. The design of a Smart Door With Automatic Lock System - Sensored Smart Door to Measure Body Temperature and Limiting the Number of Visitors is also able to make it easier for the nearest Covid-19 task force team to detect crowd points and crowds of visitors so that they can be followed up and take proper handling.